Effects of percutaneously-implanted epidural stimulation on cardiovascular autonomic function and spasticity after complete spinal cord injury: A case report - Gorgey, Ashraf S.; Goldsmith, Jacob; Alazzam, Ahmad; Trainer, Robert (Frontiers in Neuroscience, 2023)
Importance There is a revived interest to explore spinal cord epidural stimulation (SCES) to improve physical function after spinal cord injury (SCI). This case report highlights the potential of eliciting multiple functional improvements with a single SCES configuration, a strategy which could improve clinical translation. Objective To determine whether SCES intended to facilitate walking also acutely yields benefits in cardiovascular autonomic regulation and spasticity. Design Case report from data collected at two timepoints 15 weeks apart from March to June 2022 as part of a larger clinical trial. Setting Research lab at Hunter Holmes McGuire VA Medical Center. Participant 27-year-old male, 7 years post a C8 motor complete spinal cord injury. Intervention A SCES configuration intended to enhance exoskeleton-assisted walking training applied for autonomic and spasticity management. Main outcomes and measures The primary outcome was cardiovascular autonomic response to a 45-degree head-up-tilt test. Systolic blood pressure (SBP), heart rate (HR), and absolute power of the low-frequency (LF) and high-frequency (HF) components of a heart-rate variability analysis were collected in supine and tilt with and without the presence of SCES. Right knee flexor and knee extensor spasticity was assessed via isokinetic dynamometry with and without SCES. Results At both assessments with SCES off, transitioning from supine to tilt decreased SBP (assessment one: 101.8 to 70 mmHg; assessment two: 98.9 to 66.4 mmHg). At assessment one, SCES on in supine (3 mA) increased SBP (average 117 mmHg); in tilt, 5 mA stabilized SBP near baseline values (average 111.5 mmHg). At assessment two, SCES on in supine (3 mA) increased SBP (average 140 mmHg in minute one); decreasing amplitude to 2 mA decreased SBP (average 119 mmHg in minute five). In tilt, 3 mA stabilized SBP near baseline values (average 93.2 mmHg). Torque-time integrals at the right knee were reduced at all angular velocities for knee flexors (range: −1.9 to −7.8%) and knee extensors (range: −1 to −11.4%). Conclusions and relevance These results demonstrate that SCES intended to facilitate walking may also enhance cardiovascular autonomic control and attenuate spasticity. Using one configuration to enhance multiple functions after SCI may accelerate clinical translation. Clinical trial registration https://clinicaltrials.gov/ct2/show/, identifier NCT04782947.